Comparison of Resonant LLC and LCC Converters for Low-Profile Applications - Pawellek, Alexander; Oeder, Christian; Dürbaum, Thomas (European Conference on Power Electronics and Applications (EPE), August 2011, 2011)
Due to the increasingly demand for highly efficient, cost-effective and low-profile applications, resonant converter topologies are massively gaining in importance. With the LCC and LLC converter, the two most promising topologies of this converter class are presented and compared within this paper. Based on their individual configuration, both converters are analyzed in the time domain revealing the first differences and similarities. Moreover, both converter topologies are optimized with respect to a low-profile notebook adapter specification for 100 W. The main focus is placed on the magnetic design of both transformers. Finally, two prototypes using completely identical layouts are developed and measurement results are discussed concerning best operation point and overall efficiency. © 2011 EPE Association - European Power Electr.
UnivIS-Import:2015-03-09:Pub.2011.tech.IE.lselek.compar
Keywords: High power density systems; Resonant converter; Resonant-mode power supply; ZVS converters